Pengaruh Pajak Hotel Dan Pajak Restoran Terhadap Pendapatan Asli Daerah Di Sumatera Barat - Andri Wahyudi; Annisa Annisa (Akuntansi, 2023)
Regional income is the main source of financing for regional development projects. This study aims to examine the Hotel Tax and Restaurant Tax on Regional Original Income in Regencies and Cities in West Sumatra Province. This study uses a sample through the website www.kemenkeu.go.id. The data taken is the realization of the Regional Original Revenue of the Regency / City government in West Sumatra for the 2019-2021 period. Based on the sample in this study using the sensu method in which the entire population will be used as a sample in this study consisting of 7 cities and 12 districts. Hypothesis testing using panel data regression using the E Views 9.0 program. The results showed that Hotel Tax had a positive and significant effect on Regional Original Income and Restaurant Tax had a positive and significant effect on Regional Original Income.